Hypoxia stress affects the physiological responses, apoptosis and innate immunity of Kuruma shrimp, Marsupenaeus japonicus. Issue 122 (March 2022) - Wang, Panpan; Liu, Hongtao; Zhao, Sizhe; Yu, Shihao; Xie, Shumin; Hua, Songsong; Yan, Binlun; Xing, Chaofan; Gao, Huan
Abstract: For commercial aquatic animals, hypoxia phenomenon often occurs in live transport and aquaculture. In previous studies, much interest has been focused on antioxidant enzyme activities and could not present the complexities. The multifaceted responses, especially considering physiological indexes, histological structure, cell apoptosis, and immune pathways, are still unknown. In this study, we investigated the comprehensive hypoxic responses of Marsupenaeus japonicus . The results showed that the physiological indexes showed time-dependent changes upon hypoxia stress. Hypoxia stress led to significant tissue damage and cell apoptosis in the gill and hepatopancreas. Compared with the control group, the apoptosis index (AI) of the 12 h hypoxic treatment increased significantly ( p < 0.05) in the gills and hepatopancreas. Comparative transcriptome analysis identified 900 and 1400 differentially expressed genes (DEGs) in the gill and hepatopancreas, respectively. Several DEGs were related to the lysosome, glycolysis/gluconeogenesis, citrate cycle, and apoptosis, and seven of them were validated using quantitative real-time PCR. This study provided valuable clues to understanding the mechanisms underlying the hypoxic responses of M. japonicus . Highlights: The physiological indexes showed time-dependent changes upon hypoxia stress. Hypoxia stress led to significant tissue damage and cell apoptosis. A total of 900 and 1400 DEGs were detected in the gill and hepatopancreas. Glycolysis, anaerobic metabolism and TCA cycle were affected by hypoxia stress.